ANALISIS PENGENDALIAN RISIKO KECELAKAAN KERJA PADA PEKERJA TAMBANG - Sophie Zafira Tanjung; Susilawati (CV. ADIBA AISHA AMIRA, 2025)
Mining is some or all stages of activities in the framework, management and exploitation of mineral or coal mining which includes general investigations, exploration, feasibility studies, construction, mining, processing or refining, or development and utilization of minerals or coal. Based on work accident data in Indonesia from BPJS Katenagakerjaan for the period January to September 2021, it was revealed that 82 thousand cases were related to work accidents and 179 cases were related to occupational diseases (PAK), with 65% related to Covid-19. As provided by information from the Ministry of Energy and Mineral Resources (ESDM), there were 93 work accidents in the mining sector in 2021. These incidents included 36 cases considered light, 57 cases classified as heavy duty, and 11 deaths due to work accidents . The aim of this research is to find out how to control the risk of work accidents in mining workers. One of the causes of workplace incidents is directly linked to unsafe actions and unsafe conditions, which ultimately lead to the shutdown of operational processes involving individuals or equipment.